Effect of the plating parameters on the electrodeposition of Ni matrix coatings containing Ti nanoparticles. (4th March 2019) - Lekka, M.; Offoiach, R.; Revelant, F.; Fedrizzi, L.
ABSTRACT: This work focuses on the production of electrodeposited nickel matrix composite coatings containing Ti nanoparticles and on the modification of the process parameters in order to maximise the codeposited particles content as well as obtaining a uniform distribution along the coating thickness. The deposition was carried out using a Ni sulphamate plating bath with different amounts of Ti nanoparticles. The plating parameters such as current density, current type (direct, DC, or pulsed, PC) and the use of ultrasound during the deposition have been modified. The specimens produced have had their microstructure, chemical composition and microhardness analysed. It was found that the increase of the particle concentration in the plating bath up to 40 g L −1 leads to an increase of the amount of codeposited particles. The use of ultrasound prevents agglomeration of the particles, leads to a more uniform distribution and increases the Ti content. However, it induces microstructural defects in the matrix. These defects can be limited by increasing the current density or by using pulsed current.